Detailed study protocol for systematic scoping review of research on child marriage, 2000–2019 - Manahil Siddiqi; Margaret E. Greene (BMJ Open)
Introduction The global development agenda reflects greater attention to ending child marriage and supporting adolescent girls than ever before. Limited understandings of the evidence base on child marriage, however, make it challenging to assess gaps in the literature and inform policy and programming to respond to the needs of adolescent girls. The goal of this project is to systematically identify, evaluate and synthesise the global evidence on child marriage.Methods and analysis We will include articles with a thematic focus on child marriage from all geographic settings, two decades of research (2000–2019) and in four languages (English, Spanish, French and Portuguese). We will search 18 electronic academic databases (7 in English and 4 each in French, Spanish and Portuguese, with 1 overlapping database) and for the grey literature, conduct targeted hand-searches of organisations engaged in work to prevent child marriage. The databases for studies in English are PubMed, PsychINFO, Embase, CINAHL Plus, Popline, Web of Science and Cochrane Library; for studies in French, the databases will be DialNet, Directory of Open Access Journals, Science Direct and Biblioteca CCG-IBT database; in Spanish, DialNet, La Biblioteca Científica Electrónica en Línea, Red Iberoamericana de Innovación y Conocimiento Científico and Jstor and in Portuguese, Coordenação de Aperfeiçoamento de Pessoal de Nível Superior, Biblioteca Virtual em Saúde, Biblioteca Científica Eletrônica On-line and Biblioteca Digital Brasileira de Teses e Dissertações. We will also review reference lists of select articles and seek input from key authors, field practitioners and participants in international convenings. We will collect and analyse data on publication characteristics, including type of document, institutional affiliation, publication year, language, focus country and region, study objective, specific focus, research method, key findings and recommendations of the material offered for future work. The database searches for publications in English were conducted in January 2020 and we plan to complete the searches in French, Spanish and Portuguese in early 2021.Ethics and dissemination As a systematic review of already-published data, this study does not raise ethical or safety concerns. The authors plan to publish the results of the scoping review in a relevant international journal as well as present the results widely following publication. Building on this foundational work, the authors plan to conduct analyses that make use of the rich data.Registration details The study design adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. Our protocol was registered with Open Science Framework on 14 January 2020 (https://osf.io/awh8v).